Relationship between Sex, Age, Body Mass Index, and Physical Fitness with Elderly Participation - Williyanto, Septian; Kusmaedi, Nurlan; Sumardiyanto, Sumardiyanto; Nugroho, Wildan Alfia (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
The purpose of this study was to reveal the relationship between sex, age, body mass index and physical fitness with the level of active participation of the elderly in development. The research method used is descriptive correlational. Samples were taken from the sports association of the elderly who live in the Pasir Layung Village of Bandung City as many as 30 people. The results showed that there was a sex relationship to TPA with a percentage of 58.5% for male and 41.5% for female, the relationship between age and TPA with a Sig. 0.000 <Sig a with r = -0.637, the relationship between BMI and TPA is the Sig. 0,000 <Sig. a with a value of r = -0.826, and the relationship between physical fitness and TPA with the Sig. 0,000 <Sig. a with a value of r = 0.857. The conclusion of this study is that there is a relationship between sex, age, body mass index and physical fitness with the level of active participation of the elderly in development.